TINJAUAN HUKUM TERHADAP PRINSIP NASIONALITAS DALAM JUAL BELI HAK ATAS TANAH - La Ode Muhammad Muskur; La Ode Hendro Susilo (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2023)
The principle of nationality adopted in the constitution on agriculture is fully enshrined in the Property Rights Regulation. Indonesian citizens who can have land ownership rights, while foreign citizens only have land use rights, then articles 1 and 2 of the constitution are thus complied with. The aim of this research is to determine the application of the nationality principle in the purchase and sale of fundamental rights and the effect of the nationality principle on the legal force in the purchase and sale of fundamental rights.The type of research used in this research is normative-empirical law, this research deals with the implementation or implementation of positive legal provisions and factual written documents about certain legal events occurring in society. The purpose of the assessment is to verify whether the results of the application of the law on legal facts are in concreto in accordance with the provisions of the legislation. Or in other words, whether the provisions of the legislation have been properly implemented so that the stakeholders achieve their goals or not. The results of the study indicate that the application of the nationality principle. The application of the nationality principle is an effort where the Indonesian people have full land rights in the Republic of Indonesia in accordance with the provisions of the law, while foreign citizens are not granted land rights in the form of property rights. Foreigners only have the right to cultivate, the right to build and the right of use. The legal force of the sale and purchase itself is in the deed of sale and purchase (AJB) where the deed of sale and purchase is proof that the fundamental rights have been transferred to the buyer who has bought the fundamental rights (property rights). The factor that then influences the legal force of buying and selling fundamental rights based on the nationality principle itself is whether the second party in this case the buyer is still a foreigner (WNA) which is an administrative defect and cannot be registered with the National Land Agency.